PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVSDS YKPP SUNGAI PAKNING KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Misbah Misbah; Lazim N Lazim N; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low results of fourth grade students learn mathematics SDS YKPP Sungai Pakning River Bukit Batu subdistrict Bengkalis, with an average grade 62.70. While the value of minimum completeness criteria (KKM) Mathematics is 65. Among the students who totaled 27 people only 11 people who reached KKM with a percentage of 40.74 . This study is a Classroom Action Research (CAR) conducted aims to improve student learning outcomes Math class SDS IV YKPP Sungai Pakning River by implementing cooperative learning model. Data collection instruments in this thesis is the teacher activity sheet and sheet student activity and learning outcomes. This paper presents the study results of the data obtained from the average of the results of study before action 62.70 increased by 2,77% to 68.25 in cycle I. In the second cycle increased to 20,20% with an average of 75.37. The activities of teachers in the first cycle the first meeting to obtain a percentage of 45.83% with less category, at the second meeting have increased the percentage of 54.16% with less category. Furthermore, the first meeting of the second cycle of teacher activity also increased with the percentage of 62.5% to the category of pretty and at the second meeting of the second cycle increased again with the percentage of 79.16% with the good category. Activity of students in the first cycle the first meeting to obtain a percentage of 50.0% with less category, in the first cycle second meeting increased with the percentage of 58.33% with less category, the students begin to understand this cycle of learning activities by applying this learning model kooperatif.Hal characterized by the activity of students in the second cycle the first meeting with a percentage increase of 75.0% to the category enough. At the second meeting of the second cycle increased with the percentage of 91.66% with the good category. Results of the study in class IV SDS YKPP Sungai Pakning River proved that the implementation of cooperative learning model can improve learning outcomes Maths grade IV SDS YKPP Sungai Pakning River Bukit Batu subdistrict Bengkalis.Keywords: cooperative learning, Mathematics Learning Outcomes